Managing ICT Media to Enhance the Learning Quality of Pancasila Education - Dinar Dariah; Hanafiah Hanafiah (Journal of Science and Education (JSE), 2026)
The integration of Information and Communication Technology (ICT) presents a significant opportunity to enhance the quality of Pancasila Education, yet its effective implementation is hindered by managerial challenges. This study addresses the gap between the potential of ICT and its practical application by analyzing how ICT media can be systematically managed to improve learning outcomes in elementary school Pancasila Education. This research employed a qualitative methodology with a comparative, multiple-case study design at two distinct elementary schools, SDN Sukamukti in Cianjur and SDN Salammulya in Purwakarta. Data were collected through in-depth interviews with principals and teachers, non-participant observation of classroom instruction, and analysis of institutional documents. Data were analyzed using the interactive model of Miles & Huberman. The findings reveal that a systematic management process, framed by the POAC (Planning, Organizing, Actuating, Controlling) cycle, is critical for success. The planning and organization phases were crucial for aligning ICT integration with curricular goals and available resources. The implementation phase demonstrated that ICT transformed Pancasila learning from passive memorization to active engagement through interactive media. The evaluation phase provided a mechanism for continuous improvement, addressing constraints such as teacher competency and resource limitations. The effective management of ICT media is a powerful determinant in improving the learning quality of Pancasila Education. This study concludes that a structured, cyclical management approach is essential for overcoming implementation barriers and harnessing the full pedagogical potential of technology.